Function of the Diaries in El zorro de arriba y el zorro de abajo, by José María Arguedas - Liang, Shiau-Bo (2019)
This paper suggests that José María Arguedas (1911-1969) in El zorro de arriba y el zorro de abajo, interweaves diary writing, which includes reflections on the socio-political condition, on the situation of Latin-American writers, and about his own state, in order to provide self-justification with respect to his negative reception. This deconstruction of his old self in the diaries provides space to accumulate strength and "audacity" for the story; and by eliminating himself as the author, he gives voice to the mythical indigenous foxes.